Studying the most important factors affecting farmers’ adoption of solar energy in the village of Fayrouzah (Journal of Hama University, 2024)
This research aimed to study the most important factors influencing farmers’ adoption of solar irrigation in the village of Fayrouzah in the eastern countryside of Homs.The data was taken from a random sample of 375 farmers, analyzed using the binary probit regression method and the statistical analysis program SPSS, where the variable was considered The dependent variable is a binary variable that takes the value (1) if the farmer adopts solar-powered irrigation, and the value (0) if the farmer does not adopt solar-powered irrigation, and under the influence of independent variables (age - educational level - marital status - size of agricultural holding - source of information - other profession – Obtaining a loan – Energy installation prices – Regular maintenance – Economic feasibility – Experienced manpower – Energy supplies – Influence by others).The results showed that the age of the farmer, the size of the agricultural holding, the economic feasibility of solar energy, and the availability of skilled labor in installation and maintenance are among the most important factors influencing farmers’ adoption of this technology.